Heuristic Concentration and Tabu Search: A Nose to Nose Comparison - K.E. Rosing; C.S. ReVelle (Tinbergen Institute, 1997)
In 1997 two papers_new applying the metaheuristics Tabu Search (TS) and Heuristic Concentration (HC) tothe p-median problem were published in consecutive volumes of the European Journal of OperationalResearch. Here we apply the method of HC some of the data sets which were used for computationalexperience in the paper on TS and briefly set out the results.
Keywords: 330; combinatorial optimization; heuristics; integer programming; location; heuristic concentration; tabu search; Mathematische Optimierung; Theorie